Analysis of Factors Affecting Pregnancy Visits for Mother and Fetal Health - Cut Yuniwati; Fithriany; Cut Nurhasanah; Lili Kartika Sari Harahap; Silfia Dewi (Health and Technology Journal (HTechJ), 2023)
The health of pregnant women is an important aspect to pay attention to throughout the gestation period for unexpected complications to occur. Pregnancy visits play an important role in detecting any complications during pregnancy early. Many factors influence the mother in carrying out a pregnancy visit (ANC). This study aimed to analyze the factors that influence pregnancy visits for the health of the mother and fetus. This type of research is analytic with a cross-sectional. The study population was third-trimester pregnant women at the Langsa Baro Public Health Center. The sampling technique uses the total population, so the number of samples is 83 people. Data analysis used the chi-square and multiple logistic regression. The results showed that knowledge (sig. 0.002), attitude (sig. 0.001), family support (sig. 0.000), and the role of health workers (sig. 0.000) had a significant relationship with pregnancy visits. The multivariate results show that the role of health workers has the most influence on pregnancy visits by pregnant women.